БИОЛОГИЯ ВИДОВ РОДА CONVOLVULUS L., РАСПРОСТРАНЕННЫХ В СУРХАНДАРДИНСКОМ ОБЛАСТИ - Умаралиева Шодиёна Фарходжон кызы (TADQIQOTLAR, 2025)
Abstract: This article provides information on the taxonomy of species belonging to the genus Convolvulus L. within the flora of the Surkhandarya region. In the flora of the Surkhandarya region, the Convolvulaceae Juss. family is distinguished by a unique plant world. Information on the latest scientific works on their distribution, biology, and taxonomic status in the Surkhandarya region is highlighted. Currently, 1962 species of this family, belonging to 59 genera, are known on Earth [12]. 208 species of the genus Convolvulus L. have been identified on Earth [12], 23 species in Central Asia [7], and 14 species in Uzbekistan [3], of which 10 species have been recorded growing in the Surkhandarya region. Below we provide a biological description of 8 species of the genus Convolvulus L., found in this region.